Liquid-infused nanostructured composite as a high-performance thermal interface material for effective cooling - Rui Cheng; Qixian Wang; Zexiao Wang; Lin Jing; Ana V. Garcia-Caraveo; Zhuo Li; Yibai Zhong; Xiu Liu; Xiao Luo; Tianyi Huang; Hyeong Seok Yun; Hakan Salihoglu; et al. (Nature Communications)
Abstract Effective heat dissipation remains a grand challenge for energy-dense devices and systems. As heterogeneous integration becomes increasingly inevitable in electronics, thermal resistance at interfaces has emerged as a critical bottleneck for thermal management. However, existing thermal interface solutions are constrained by either high thermal resistance or poor reliability. We report a strategy to create printable, high-performance liquid-infused nanostructured composites, comprising a mechanically soft and thermally conductive double-sided Cu nanowire array scaffold infused with a customized thermal-bridge liquid that suppresses contact thermal resistance. The liquid infusion concept is versatile for a broad range of thermal interface applications. Remarkably, the liquid metal infused nanostructured composite exhibits an ultra-low thermal resistance <1 mm² K W-1 at interface, outperforming state-of-the-art thermal interface materials on chip-cooling. The high reliability of the nanostructured composites enables undegraded performance through extreme temperature cycling. We envision liquid-infused nanostructured composites as a universal thermal interface solution for cooling applications in data centers, GPU/CPU systems, solid-state lasers, and LEDs.